MENUMBUHKAN RASA BANGGA GENERASI MUDA TERHADAP BAHASA INDONESIA SEBAGAI BAHASA NASIONAL DAN INTERNASIONAL - Werdiningsih, Endang (Jurnal Likhitaprajna, 2016)
Indonesian has become a state language and national language over the years is not able to be proud of our young people. The phenomenon was apparent when they speak not fully understand about Indonesian.The lack of pride that one of them is influenced by the government, the public, and teacher in implementing the learning process. With a variety of regulations have been promulgated on the use of Indonesian, government has not do real action against violations committed by the public. The Society is more proud to use a foreign language than Indonesian, and young people are less interested in learning Indonesian so that learning can notcreate an attitude of pride in his own language.Keywords: pride, youth, Indonesian